Razão em transe: o barroco e o cinema de Glauber Rocha - Rodrigo Cassio Oliveira (2014)
After Terra em Transe (1967), Glauber Rocha was considered the author of a baroque cinema. This work discusses the possible meanings of that classification in aesthetics and philosophy of art. To this end, we analyze baroque theories produced by 20th century authors, highlighting their contributions to the study of images and film. The relationship between baroque, classicism and modernity; the hypothesis of cinematic realism; the subjective positioning on the experience with the movie; the critique of cultural industry and an effort to affirm Brazilian and Latin American identities are the topics involved in Rochas interventions. This research considers Glauber Rochas movies, but also his books, essays, texts and interviews. In this sense, we emphasize the comparison of Eztetyka da Fome (1965) and Eztetyka do Sonho (1971) as two political statements mediated by Terra em Transe, whose differences indicate the particular appropriation of baroque aesthetic by Glauber Rocha. This orientation marked his dissent with certain post-1968 left-wing criticism in France, reflected in Jean-Luc Godards affiliation with the Dziga Vertov Group. In that context, for Rocha, the rejection of spectacle meant the destruction of cinema.